Esto es coraje - Sperry, Armstrong, 1897-1976 (Barcelona : Editorial Noguer, 1997)
Based on a Polynesian legend, this is the story of a youth who overcomes his fear of the sea and proves his courage to himself and his tribe.
Translation of: Call it courage.
Newbery Award 1941.
In Spanish.
Keywords: Survival -- Juvenile fiction; Polynesia -- Juvenile fiction